The Impact of the Free Nutritious Meal Program (MBG) on the Nutritional Status of Preschool-Aged Children at the RA Al Ismaliyah 2 Sawiji Kindergarten - Ana Farida Ulfa; Zuliani Zuliani; Andi Yudianto (Adi Husada Nursing Journal, 2026)
Nutritional issues in children are a priority in child health. In addition to being susceptible to disease, nutritional problems can lead to decreased productivity in adulthood, ultimately impacting socioeconomic issues. The MBG program supports child growth to improve nutritional status, cognitive development, and academic achievement. This study aimed to determine the effect of the MBG program on the nutritional status of preschool-aged children. The research method used was quantitative with a pre-experimental design (a single-group pretest-posttest design). The study population was students at KB-RA Al Islamiyah 2, using a purposive sampling technique, with the following criteria: students present at the time of the study and a maximum age of 72 months. The KMS 2023 was used as a parameter to evaluate the children's nutritional status. Children's weight was measured before and after MBG administration over a three-month period. The study results showed no effect of the MBG program on the nutritional status of preschool children at KB-RA Al Islamiyah 2. This condition is influenced by unhealthy eating habits. Inappropriate eating habits can lead to malnutrition or overnutrition in children. Another condition that influences nutritional status is the mother's knowledge and ability to choose and prepare a variety of nutritious and attractive foods for the daily menu.